Public trust and media influence on anxiety and depression levels among skilled workers during the COVID-19 outbreak in Serbia - Marković, Ivan; Nikolovski, Srdjan; Milojević, Stefan; Živković, Dragan; Knežević, Snežana; Mitrović, Aleksandra; Fišer, Zlatko; Djurdjević, Dragan (Vojnosanitetski pregled, 2020)
Background/Aim. Along with the great impact of 2019 coronavirus disease (COVID-19) on physical health, social functioning, and economy, this public health emergency has significant impact on mental health of people as well. The aim of this study was to assess the impact of outbreak-related information and public trust in the health system and preventive measures during the COVID-19 outbreak in Serbia in 2020 on levels of anxiety and depression in education, army and healthcare professionals. Methods. An anonymous questionnaire was disseminated to skilled professionals working in fields of education, army, and healthcare. The questionnaire included the Beck Anxiety Inventory, Zung Self-Rating Depression Scale, as well as the section assessing the perceived disturbance by the outbreak-related information and the trust of participants in healthcare system and preventive measures proposed by the crisis team. Results. Out of 110 subjects enrolled in this study (mean age 35.25 ± 9.23 years), 59.1% were women. Among healthcare workers, the frequency of perceiving outbreak-related information available in public media as disturbing, as well as the average level of anxiety, were higher compared to the group of army professionals (p < 0.05). Women also perceived outbreak-related information available in public media as disturbing in a higher percentage compared to men (p < 0.01), and had higher levels of anxiety (p = 0.01) and depression (p < 0.05). The lack of public trust was associated with higher levels of depression, and the perception of outbreak-related information as disturbing with higher levels of both anxiety and depression. Conclusion. Significant perception of outbreak-related information as disturbing among healthcare workers, as well as the lack of trust in healthcare system and preventive measures proposed by the crisis team are important factors influencing the mental state. This finding has the guiding purpose for competent institutions to make efforts to increase public trust, as one of the important preventive measures, in order to preserve and improve the mental well-being of the population in outbreak conditions.